1982
DOI: 10.1042/cs0630087
|View full text |Cite
|
Sign up to set email alerts
|

Activation by Exercise of Human Skeletal Muscle Pyruvate Dehydrogenase In Vivo

Abstract: 1. The activity of pyruvate dehydrogenase in its active and inactive forms was measured in biopsy samples obtained from the vastus lateralis muscle of healthy subjects before and after exercise. 2. At rest, 40 +/- 4% (mean +/- SEM) of the enzyme was in the active form. 3. After progressive aerobic exercise to exhaustion (n = 5), 88 +/- 2.3% was in the active form. 4. After intermittent supramaximal short-term exercise (1 min exercise, 3 min rest) to exhaustion (n = 6), 60 +/- 2.2% was in the active form. 5. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The exercise-induced activation of PDH a activity corresponds well with previous human studies on vastus lateralis (18,22,26,31,32). In these studies, the intensity has in general been moderate [45-55% maximal oxygen consumption (V O 2 max ) or watt max ], and only one study examined PDH a activity during intense exercise (6), where subjects performed graded 10-min sessions of exercise at 60 and 90% V O 2 max .…”
Section: Discussionmentioning
confidence: 58%
“…The exercise-induced activation of PDH a activity corresponds well with previous human studies on vastus lateralis (18,22,26,31,32). In these studies, the intensity has in general been moderate [45-55% maximal oxygen consumption (V O 2 max ) or watt max ], and only one study examined PDH a activity during intense exercise (6), where subjects performed graded 10-min sessions of exercise at 60 and 90% V O 2 max .…”
Section: Discussionmentioning
confidence: 58%
“…Especially PDK has proven to be highly regulated at the mRNA level in skeletal muscle in recovery from exercise (33,35), and acute regulation of PDK4 expression has been suggested to play a role in restoring muscle glycogen stores after exercise (34). The activity of PDH in the active form (PDHa) increases in human skeletal muscle during exercise as first demonstrated by Ward et al (45) and an associated dephosphorylation of PDH-E1␣ has been shown more recently (16,17,32). The exercise-induced PDHa activation increases with increasing power output (12), and the upregulation of PDHa activity in the initial part of an exercise bout occurs concomitant with increased carbohydrate use (17,47).…”
mentioning
confidence: 79%
“…Thus, several studies have reported a decrease in PDH activity in response to fasting and alloxan-streptozotocin-induced diabetes in rat muscle (for review, see Roche et al 2001;Sugden & Holness, 2003) and in response to a high-fat diet in human muscle (Putman et al 1993). In addition, an exercise-or contraction-induced increase in PDH activity has been demonstrated in both rat (Hennig et al 1975;Hagg et al 1976;Dohm et al 1986;Brozinick et al 1988) and human (Ward et al 1982;Putman et al 1993) muscle during exercise or contractions of £2 h duration. Determination of PDH activity during exercise of >2 h duration has not been performed until recently (see p. 224).…”
Section: Structure and Regulation Of The Pyruvate Dehydrogenase Complexmentioning
confidence: 99%
“…Possible role of pyruvate dehydrogenase kinase 4 expression in substrate utilization during exercise As mentioned earlier, several studies have previously shown that PDH activity is rapidly increased during the initial 1-2 h of exercise (Hennig et al 1975;Hagg et al 1976;Ward et al 1982;Dohm et al 1986;Brozinick et al 1988;Putman et al 1993). The finding that PDK4 transcription and mRNA content increase during prolonged exercise, together with the known switch occurring in substrate utilization in skeletal muscle during prolonged exercise, has led to the proposal that increased PDK4 expression might have an effect on PDH activity during prolonged exercise.…”
Section: Potential Transcription Factors Involved In Regulating the Pmentioning
confidence: 99%